A study on the health seeking behaviour among the geriatric population in the urban field practice area of JJM Medical College Davangere - Dhar, Ruchi; Vidya, G. S. (International Journal Of Community Medicine And Public Health, 2020)
Background: According to census 2011 the elderly population aged 60 years and above account for 8% of total population and is projected to rise to 12.4% by the year 2026. Health status is an important factor that has a significant impact on quality of life. The elderly is one of the most vulnerable and high risk groups in terms of health status and their health seeking behaviour is crucial in any society. Methods: A community based cross sectional study was carried out for a period of 1 year for which a predesigned and semi-structured questionnaire was used and a total of 440 elderly were interviewed by house to house survey. Results: In our study it was found that the majority of the subjects (36.8%) were in the age group of 60-64 years, 52.5% were illiterate, 51.1% were unemployed and 49% belonged to class IV socio economic status. Any degree of formal schooling was found to be associated with better health seeking behavior. Majority of the subjects (58%) visited a government health facility in case of an illness and the main reason that was stated for not visiting a health facility was that they suffered from mild discomfort (44.4%) and did not consider it necessary to visit a health facility. Conclusions: It was observed that more number of males visited a health care facility in case of an illness, 241 (92.7%) whereas only 154 (85.6%) females visited a health facility in case of an illness. This difference was found to be statistically significant.